CULTURAL SYNTHESIS IN ISLAMIC PEDAGOGY: NURTURING IDENTITY THROUGH THE INTEGRATION OF LOCAL HERITAGE IN EDUCATIONAL PRACTICES - Muhajir Musa; Miftah Ulya; Mulyoto; Agung Putra Mulyana; Muhammad Irfan (Adisam Publisher, 2024)
This literature review explores the dynamic relationship between local culture and Islamic pedagogy, focusing on nurturing identity by integrating local heritage into educational practices. Recognizing the pivotal role of cultural synthesis, the review spans historical perspectives, theoretical foundations, empirical studies, and pedagogical approaches. Key findings underscore the enriching impact of incorporating local cultural elements in Islamic education, fostering a more engaging and relevant learning environment. The synthesis reveals common themes, such as the adaptability of Islamic education to diverse cultural contexts and the symbiotic relationship between Islamic principles and local cultural elements. The discussion explores implications for practice and research, emphasizing the significance of cultural diversity in shaping effective Islamic education. Recommendations include promoting cultural competence among educators, integrating local culture into curriculum design, and fostering dynamic, inclusive pedagogical approaches.